"Vi går inn i det private rommet til pasienten". Sykepleieres erfaring med helsefremmende arbeid i somatiske polikliniske - Anne Svelstad Evju; Gøril Salomonsen Klette; Anne Kasen; Terese Bondas (Septentrio Academic Publishing, 2014)
Nurses experiences of health promotion with patients in somatic outpatient clinics The aim is to describe and understand nurses' experiences of health promotion with patients, who have been recommended to change their lifestyles when cared for in outpatient clinics. Semi-structured in-depth interviews were carried out with a sample of 7 nurses, who cared for patients, suffering  from diabetes, obesity and COPD. A qualitative content analysis was used. The findings highlight the importance of creating trust to gain insight into the patient's way of living, which is referred to as 'the patient's private health space'. The change interventional dialogue between the patient and the nurse was created by mapping out the patient's potential for change, and by trying to make the patient responsible for their lifestyle by continuous follow up, long-term support and guidance. The nurses viewed individual adaptation of health promotion in relation to each patient as essential. The patients are challenged to use their own resources and are guided in regard to their own goals. The nurses role as the activator of change is important.